2008
DOI: 10.1097/brs.0b013e31817b8fed
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Changes of Discs and Facet Joints in Lumbar Total Disc Replacement Using ProDisc II

Abstract: After TDR using ProDisc II, the degenerative changes in the discs and facets at the adjacent segments appeared to be minimal. However, in 29.3% of the TDR segments, the facet joints presented PFA, which was more common in female, malposition of prosthesis on frontal plane, and 2-level TDR in a minimum 2-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 25 publications
3
47
0
4
Order By: Relevance
“…"SKIPPED" LEVEL DISC DEGENERATIONbody arthroplasty techniques were used to facilitate, in premise, motion preservation (42,44,45). In fact, using such a model for reference may be more appropriate, because, as some investigators contend, the escalating severity of disc degeneration has been associated with an increase in segmental motion (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…"SKIPPED" LEVEL DISC DEGENERATIONbody arthroplasty techniques were used to facilitate, in premise, motion preservation (42,44,45). In fact, using such a model for reference may be more appropriate, because, as some investigators contend, the escalating severity of disc degeneration has been associated with an increase in segmental motion (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…A preoperatively existent high-grade facet joint degeneration (FJD) can especially lead to inferior clinical results; therefore, FJD was suggested as a contraindication for this procedure [18]. However, facet joint forces may increase after TDR followed by a de novo development or the progression of preoperatively existing initial FJD in a relevant percentage of patients (20-36 %) with a resulting inferior clinical outcome [19][20][21][22][23]. In a prospective study, Siepe et al [23] found that FJD appeared more frequently at the index level compared with the adjacent levels and significantly more frequently at the lumbosacral junction compared with the levels above it.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, patients with FJD progression after TDR present with inferior clinical results a few month postoperatively [23], which suggests that FJD itself may not be the only cause of pain or functional impairment. Several factors, such as malposition in the frontal plane, the grade of restoration of the disc height by segmental distraction, or the consecutive changes of the local sagittal curve with increased segmental lordosis, may affect facet joint forces after TDR [20,25,26]. In our probabilistic finite element model (FEM) analysis [27], we demonstrated that a segmental misalignment in the sagittal plane after TDR with an anterior or posterior shift of the superior vertebra leads to a significant increase in facet joint contact or capsule tensile forces.…”
Section: Introductionmentioning
confidence: 99%
“…Controversy still exists regarding whether TDR can prevent adjacent segment degeneration in the long term [23][24][25][26][27]. To assess the role of any new treatment method, long-term clinical results need to be evaluated in clinical studies with adequately sized patient cohorts and sufficient long-term results.…”
Section: Introductionmentioning
confidence: 99%